State of the art issues in contemporary mass communication - Shimkin, David; O'Connor, Helene; Stolerman, Harold
This book is an updated anthology of 66 essays that examine the socio-cultural, political and economic, legal and ethical issues raised by the media in the context of current events and technological advances. As you examine this new mass communication reader, please note the following features: